Wastu Citra as an Indonesia Regionalism Local Wisdom: Phenomenology Studies from Butet’s House - Stephen Y Loanoto (Talenta Publisher, 2019)
There is a theory about regionalism from Kenneth Frampton, “Critical Regionalism”. This theory is from western culture, and have some mismatch with eastern culture, especially Indonesia. In other side Indonesia had some theory from Mangunwijaya, “Wastu Citra”. The main question is what the connection between “Wastu Citra” and “Critical Regionalism”. This research will be held qualitative from phenomenology studies to test Butet’s House which is designed by Eko Prawoto. The theory become the parameter for the test. The purpose of this research is to enhance Indonesia regionalism theory. As the result, WastuCcitra theory enhance Frampton regionalism theory in the context of Indonesia. As a conclusion Manguwijaya ideas Wastu Citra could be the parameter of Indonesian Regionalism Architecture. Keyword: Wastu Citra, Regionalism, Critical Regionalism, Architecture Theory.